Green computing in network security : energy efficient solutions for business and home - Sharma, Deepak Kumar; Gupta, Koyel Datta; Dwivedi, Rinky (Boca Raton : CRC Press, 2022)
"This book focuses on green computing-based network security techniques and addresses the challenges involved in practical implementation. It also explores the idea of energy-efficient computing for network and data security and covers the security threats involved in social networks, data centers, IoT, and biomedical applications. Green Computing in Network Security: Energy Efficient Solutions for Business and Home includes analysis of green-security mechanisms and explores the role of green computing for secured modern internet applications. It discusses green computing-based distributed learning approaches for security and emphasizes the development of green computing-based security systems for IoT devices. Written with researchers, academic libraries, and professionals in mind so they can get up to speed on network security, the challenges, and implementation processes"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measures; Computer networks -- Environmental aspects; TECHNOLOGY / Manufacturing; COMPUTERS / Networking / Security; COMPUTERS / Computer Vision & Pattern Recognition